Playing Football Creating Education Character In Youth Perspective In Nighborhood Environment - Bahagia, Bahagia; wibowo, Rimun; Rangkuti, Zulkifli; Noor, Zakky Muhammad (Universitas Pahlawan Tuanku Tambusai, 2021)
The objective of this research to discover character value in playing football from a youth perspective in nighborhood football team. The research method approach exerts qualitative and ethnographic. The method is implied because the research intends to find out character value in football playing based on community perspective in nighborhood football group. The data are gathered with an in-depth interview. Sample are selected through purposive technique. The result is probed meticulously through triangulation technique and triangulation sources. The result shows that playing football has numerous value in creating character including teamwork, honesty, responsibility, role in society, and Sportif value. The other is playing football have social capital value because football match creating social networking, trusting, solidarity, mutual assisting and social connection among the member in group or group of a competitor. The other is to vanish some of the ailment such as heart attack, obesity, abolish the rate of human stress, and lung ailment. Lastly, it can improve the prosperity of societies around because the community have the opportunity to trade some of the meal and drink when the football is conducted